Functional MRI in pain: A valuable and/or reliable diagnostic tool for your pain patient?. (July 2014) - Patijn, Jacob
Abstract : In pain research, functional magnetic resonance imaging (fMRI) plays an increasingly important role, which raises questions about the clinical significance of fMRI for the treatment and diagnosis of pain in general. All the more so because some publications suggest replacing the 'subjective"'visual analogue scale pain score with the 'objective' results in fMRI. The fMRI technique as such and its relation to pain in research conditions has a large number of objections. One of the major limitations is the fact that in a very limited number of fMRI studies (8%), the results are reproduced within the study format itself (test–retest). This makes interpretation and mutual comparison of the fMRI studies extremely difficult. Therefore the clinical value of fMRI for treatment and diagnosis is hard to estimate.